El Agua y la Revolución en Bolivia: Una vista sobre la Cultura Hidráulica Demócrata - Vitz, Matthew (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2024)
Book Review Sarah T. Hines. Water for All: Community, Property, and Revolution in Modern Bolivia (Berkeley: University of California Press, 2022).